Marine Fishes of Caño Island Biological Reserve: Reef fish community structure and updated list for the coastal fish. - Salas, Eva; Sánchez-Godínez, Cristina; Montero-Cordero, Andrea (Revista de Biología Tropical, 2015)
Biogeographically, the Caño Island Biological Reserve (CIBR) is of strategic importance, since it is located in the center of the Panamic Province (Costa Rica and Panama), characterized by a peak in fish species richness within the Tropical Eastern Pacific (TEP). Despite its importance, fish community structure around the island has not been deeply studied, and coastal fish diversity records need to be updated. The aims of the study were: 1) to describe the community structure of the reef fish community of CIBR and 2) to update the list of the coastal fish species recorded until today. For the first objective, 50 stationary fish counts were conducted at 10 locations around Caño Island, in which 79 species, belonging to 32 families, were registered. The most abundant family was Pomacentridae, and the most abundant species was Chromis atrilobata. Planktivorous and carnivorous fish were the most abundant. The existence of a relationship between coral cover and the presence of herbivorous grazers was highlighted within the analysis. Additionally, species composition was compared by site and this revealed that “El Barco” has an abundant presence of snappers. For the second objective, published fish species records were collected for the CIBR and 35 new records were added, for a total of 212 coastal fish species, which represents approximately 17% of coastal fish diversity in the TEP. This work presents a baseline for fish monitoring and mangement measures in this marine protected area.